Adherence to the Mediterranean Lifestyle and Desired Body Weight Loss in a Mediterranean Adult Population with Overweight: A PREDIMED-Plus Study - Bouzas, Cristina (Nutrients, 2020)
Background. Body weight dissatisfaction is a hindrance to following a healthy lifestyle and it has been associated with weight concerns. Objectives. The aim of this study was to assess the association between the adherence to the Mediterranean lifestyle (diet and exercise) and the desired body weight loss in an adult Mediterranean population with overweight. Methods. Cross-sectional analysis in 6355 participants (3268 men; 3087 women) with metabolic syndrome and BMI (Body mass index) between 27.0 and 40.0 kg/m(2) (55–75 years old) from the PREDIMED-Plus trial. Desired weight loss was the percentage of weight that participants wished to lose. It was categorized into four cut-offs of this percentage (Q1: <10%, n = 1495; Q2: 10–15%, n = 1804; Q3: <15–20%, n = 1470; Q4: ≥20%, n = 1589). Diet was assessed using a validated food frequency questionnaire and a 17-item Mediterranean diet questionnaire. Physical activity was assessed by the validated Minnesota-REGICOR and the validated Spanish version of the Nurses’ Health Study questionnaire. Results. Participants reporting higher percentages of desired weight loss (Q3 and Q4) were younger, had higher real and perceived BMI and were more likely to have abdominal obesity. Desired weight loss correlated inversely to physical activity (Q1: 2106 MET min/week; Q4: 1585 MET min/week. p < 0.001) and adherence to Mediterranean diet (Q1: 8.7; Q4: 8.3. p < 0.001). Conclusions. In older Mediterranean individuals with weight excess, desired weight loss was inversely associated with Mediterranean lifestyle adherence. Deeply rooted aspects of the MedDiet remained similar across groups. Longitudinal research is advised to be able to establish causality.